Perception of Layperson Regarding Buccal Corridor in Smile Esthetics (Orthodontic Journal of Nepal, 2025)
Introduction: Attractive smile plays an important role in an individual’s overall personality and confidence. The buccal corridor space (BCS), defied as the dark space between the corners of the mouth and the buccal surfaces of posterior teeth during a smile, is one of the various factors affecting smile esthetics. The aim of this study was to assess the perception of BCS among Nepali laypersons and its influence on smile attractiveness.Materials and Methods: A descriptive cross-sectional study was conducted at Kathmandu Medical College from 2022 June to 2023 December after receiving ethical approval from institutional Review Committee of Kathmandu Medical College. Convenience sampling method was used to select 290 participants of age 20–50 years. The selected participants assessed digitally modified smile photographs with BCS percentages of 0%, 4%, 8%, 12%, and 16%, and rated the attractiveness.Results: It was found that 62.1% (180) of participants were aware of BCS, and 67.9% (197) believed its presence affected smile attractiveness. The majority, that is 234 (80.7%) preferred minimal or no BCS, with rating of 0% BCS as the most attractive by 120 (41.4%) and 16% BCS as very unattractive by 220 (77.2%). Conclusion: Wide smiles with little or no buccal corridor were preferred over narrow smiles with wide BCS by Nepali population. Conclusion: Wide smiles with little or no buccal corridor were preferred over narrow smiles with wide BCS by Nepali population.